Communicating the complexity of integrating information systems: a case study of the procurement of a payroll-personnel system. (1st September 2004) - Waring, Teresa
Modern organisations both in the private and public sector are seen to be increasingly reliant, in terms of achieving improvements and service targets, on the efficient provision of information to enable administrative and managerial decision making. A key barrier to effective ICT introduction and integration of information systems has been identified as the complex social, organisational and political issues endemic within organisations, preventing true discourse. This paper describes how an approach based upon some of the emancipatory principles of Jurgen Habermas may be used to develop an innovative approach to participative process and information flow modelling. This approach was used within a UK Hospital Trust in the north east of England to facilitate the integration of two departments and the procurement of a computerised payroll-personnel system. The results of the Action Research Project are described and conclusions drawn as to the success of the approach and the role of the systems analyst within this type of project.